'Think different': a qualitative assessment of commercial innovation for diabetes information technology programs. - Rupcic S; Tamrat T; Kachnowski S (Diabetes Technology & Therapeutics, 2012)
Abstract Background: This study reviews the state of diabetes information technology (IT) initiatives and presents a set of recommendations for improvement based on interviews with commercial IT innovators. Materials and Methods: Semistructured interviews were conducted with 10 technology developers, representing 12 of the most successful IT companies in the world. Average interview time was approximately 45 min. Interviews were audio-recorded, transcribed, and entered into ATLAS.ti for qualitative data analysis. Themes were identified through a process of selective and open coding by three researchers. Results: We identified two practices, common among successful IT companies, that have allowed them to avoid or surmount the challenges that confront healthcare professionals involved in diabetes IT development: (1) employing a diverse research team of software developers and engineers, statisticians, consumers, and business people and (2) conducting rigorous research and analytics on technology use and user preferences. Conclusions: Because of the nature of their respective fields, healthcare professionals and commercial innovators face different constraints. With these in mind we present three recommendations, informed by practices shared by successful commercial developers, for those involved in developing diabetes IT programming: (1) include software engineers on the implementation team throughout the intervention, (2) conduct more extensive baseline testing of users and monitor the usage data derived from the technology itself, and (3) pursue Institutional Review Board-exempt research.